Design and fabrication of hybrid tig/heating and mig welding torch holder - Mohamad Zulhilmi, Rosli (2013)
This study is about designing and fabricating a hybrid heating/TIG and MIG welding torch holder. The objectives of this project are to design and fabricate a hybrid heating/TIG and MIG welding torch holder which can be used on the automatic welding machine. Besides that, the study validates the effectiveness of the torch holder through a welding process on the automatic welding machine which is available in Faculty of Mechanical Engineering. The three-dimensional modeling of the holder was developed by using the SolidWorks™ engineering drawing software. The fabrication process such as material marking, cutting, drilling, tapping, milling and finalizing the holder by painting was conducted. Other than that, the validation process was performed by using automatic welding machine. The results of testing the product were also discussed in this thesis. As a conclusion, the final product achieves the objective of this Final Year project.